Mulher e carnaval: mito e realidade (análise da atuação feminina nos folguedos de Momo desde o entrudo até as escolas de samba) - Simson, Olga R. de Moraes von (Revista de História, 1992)
This study points to the analysis of the female presence in the Brazilian Southeastern carnival. The historical perspective surpasses the preoccupations of this study showing differences of opinion between observers. In 1855, limitations toward the participation of women in carnival began and a greater opening has only occured recently in Rio de Janeiro.